APPLICATION OF TRANSCRANIAL MICROPOLARIZATION AND THE NEURAC METHOD ON THE REDCORD SYSTEM IN THE COMPLEX RECOVERY OF PATIENTS AFTER SCI - Толок, Віктор; Бражанюк, Андрій (SWorldJournal, 2023)
The article is devoted to the theoretical justification and practical confirmation of the effectiveness of the combination of transcranial micropolarization and the Neurac technique on the Redcord system in the comprehensive program of physical rehabilita